1979
DOI: 10.1037/0022-0663.71.3.328
|View full text |Cite
|
Sign up to set email alerts
|

How characteristics of student essays influence teachers' evaluations.

Abstract: This article explores the question of why competent evaluators award the ratings they do to college students' expository essays. Essays were rewritten to be stronger or weaker in four categories: content, organization, sentence structure, and mechanics. Twelve evaluators first used a 4-point holistic rating scale to judge the essays' quality. Then they rated whether each of the four rewriting categories in each rewritten essay was strong or weak (perceptions). Analyses of variance revealed content and organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 12 publications
1
47
0
1
Order By: Relevance
“…Eckes, 2012Eckes, , 2015Engelhard, 1994;Lumley, 2002;Myford & Wolfe, 2009;Weigle, 1998) eller vurdering relatert til tekstlingvistiske trekk (Freedman, 1979;Fritz & Ruegg, 2013;Wolfe, Song, & Jiao, 2016;Xie, 2015;Ö stlund-Stjärnegårdh, 2002). Vår studie har eit anna utgangspunkt: når oppgåver er sjangerlause, vil ein føresetnad for at vurderingane ikkje skal sprike, vere at ein møter tekstar med same lesemåte.…”
Section: Gb Skar and Aj Aasenunclassified
“…Eckes, 2012Eckes, , 2015Engelhard, 1994;Lumley, 2002;Myford & Wolfe, 2009;Weigle, 1998) eller vurdering relatert til tekstlingvistiske trekk (Freedman, 1979;Fritz & Ruegg, 2013;Wolfe, Song, & Jiao, 2016;Xie, 2015;Ö stlund-Stjärnegårdh, 2002). Vår studie har eit anna utgangspunkt: når oppgåver er sjangerlause, vil ein føresetnad for at vurderingane ikkje skal sprike, vere at ein møter tekstar med same lesemåte.…”
Section: Gb Skar and Aj Aasenunclassified
“…The danger is not always realized; research by Page and by Quellmalz et al (1982) shows that individual multitrait ratings can produce unique variance. On the other hand, research by Sarah Freedman (1979) demonstrates the powerful associative, or halo, effect that can undermine the validity of analytic subscores. Chi-square analysis revealed significant correlations of "content" with "organization" and of "sentence structure" with "mechanics" in a group of essays.…”
Section: Scoring Methods For Direct Assessmentmentioning
confidence: 99%
“…However, the raters in Freedman's (1979) study said that organization was the second most difficult construct to assess with the content construct being the most difficult. Although raters find organization to be important, assessing and measuring organization is a challenge.…”
Section: Literature Review Defining Organizationmentioning
confidence: 99%
“…There was a tendency for teachers to provide more feedback on content and organization than sentence structure and mechanics in the L1 setting. Freedman (1979) also conducted a study on raters' perceptions of a piece of academic writing and found that the rewriting of essays to be stronger in content and organization had a greater impact on scores in comparison to those that were rewritten to be stronger in sentence structure and mechanics. It can be concluded from these studies that raters consider organization to be of great importance in academic essays.…”
Section: Literature Review Defining Organizationmentioning
confidence: 99%
See 1 more Smart Citation